Clinical features of gestational thrombocytopenia difficult to differentiate from immune thrombocytopenia diagnosed during pregnancy. Issue 1 (28th August 2014) - Kasai, Junko; Aoki, Shigeru; Kamiya, Natsuko; Hasegawa, Yoshimi; Kurasawa, Kentaro; Takahashi, Tsuneo; Hirahara, Fumiki
Abstract Aim To investigate the clinical features of gestational thrombocytopenia (GT) difficult to differentiate from immune thrombocytopenia (ITP) during pregnancy. Methods The January 2000–December 2012 hospital database was analyzed to identify women with ITP or GT (after excluding other possible causes of thrombocytopenia) among those first noted to have platelet counts of less than 100 000/μL during pregnancy. The maternal characteristics, platelet count fluctuations and pregnancy outcomes were compared between women with ITP and GT. Results There were 23 pregnancies (22 women) with thrombocytopenia (GT, 13; ITP, 10). The GT group included five twin pregnancies (38.5%), whereas all pregnancies of the ITP group were singleton pregnancies, with significantly more twin pregnancies in the GT group (P = 0.046). Thrombocytopenia in the first trimester occurred in 70% (7/10) of ITP cases and 23.1% (3/13) of even GT cases. The nadir platelet count was less than 70 000/μL in 100% (10/10) of ITP cases and 30.8% (4/13) of GT cases (P < 0.001). Maternal treatment was required in 80% (8/10) of ITP cases, but in none of the GT cases. The pregnancy outcomes were favorable in both groups, and no case required fetal treatment. Conclusion Gestational thrombocytopenia with platelet counts of less than 10 0000/μL occurred more frequently in twin pregnancies. Although onset of thrombocytopenia in the first trimester and a platelet count of less than 70 000/μL is more common in ITP, these findings were not uncommon in GT. Differentiation between ITP and GT may be feasible only with post‐partum changes in the platelet count.